Sun Bathing in the Salt Pond Re-making the Image of Tropical Tourism in Antigua and Barbuda - Donaldson, Sarah Robyn (University of Waterloo, 2018)
A tropical paradise – lush green palm trees and white sandy beaches – is what comes to mind when a tourist envisions the perfect Caribbean destination. Yet, ironically this idealized nature is highly transformed by tourism itself. Tourism is one of the most destructive activities in coastal zones: mined white sand is deposited to replenish eroding beaches or create new ones; wetlands are dredged and filled for beach front resort development; and resort vegetation is heavily watered in countries that face water scarcity. This thesis exposes how these frictions are hidden from the idealized images of tropical tourism and questions the role these images play in intensifying three main contradictions of Global Tourism. Antigua and Barbuda, a small twin-island nation in the North-East region of the Caribbean Sea, is one of the most extreme cases of a national economy relying on tourism in the world; 80% of their Gross Domestic Product is generated by Global Tourism and its related activities1. While tourism in Antigua and Barbuda has been extremely successful in economic terms, natural ecosystems have been sacrificed in its pursuit. This thesis proposes new narratives which re-make three dominant postcard images of global tourism in Antigua. Sleeping on the Reef attempts to alter the role of the quintessential beach front developments at Dickenson’s Bay. From disruptive intruder to active participant, the development itself provides the structural framework for an artificial reef. This generates new habitats, expands micro-economies, and re-establishes protective ecosystems. Hiking the Landfill endeavours to combine two generated wastes of Cruise Ship Tourism - dredged fill and solid waste - to reconstruct The Flashes salt marsh landscape which was buried by these excesses. Sunbathing in the Salt Pond challenges the artificial and privatized landscape created by the Jolly Harbour development by re-positioning tourism as a node, rather than a container, within a much larger network of public and ecological programming. The deconstruction of the resort integrates it within its place; the Jolly Harbour Golf Course Fairway is eroded away, eliminating the need for fertilizers and excess water consumption; and an expanded coastline allows for greater public access.